Dyslipidemia among patients with type 2 diabetes mellitus visiting Specialized Center for Diabetes and Endocrinology - Fadhil, Badri; Abdul Jabbar, Mohammed (AL-Kindy College Medical Journal, 2014)
Background:The most common pattern of dyslipidemia in diabetic patients is increased triglyceride (TG) and decreased HDL cholesterol level, The concentration of LDL cholesterol in diabetic patients is usually not significantly different from non diabetic individuals, Diabetic patients may have elevated levels of non-HDL cholesterol [ LDL+VLDL]. However type 2 diabetic patients typically have apreponderance of smaller ,denser LDL particles which possibly increases atherogenicity even if the absolute concentration of LDL cholesterol is not significantly increased. The Third Adult Treatment Panel of the National Cholesterol Education Program (NCEP III) and the American Heart Association (AHA ) have designate diabetes as a coronary heart disease (CHD) equivalent and recommended treatment of LDL-c to < 2.6 mmoll (